Characteristics of the Health Problems Among International Travelers Visiting International Hospital in Bali - Putu Indah Budi Apsari; Putu Arya Suryanditha; Ni Wayan Widhidewi; Dewa Ayu Putri Sri Masyeni (Warmadewa University, 2023)
Bali is one of the most popular tourist destinations in Indonesia. As one of the islands in a tropical country, Bali has its own risk of disease transmission. The increasing number and pattern of international travelers can affect morbidity and mortality. Research on disease problems among international travelers in travel destination countries is rarely reported. This study examines health problems concerning foreign tourists visiting hospitals in Bali. This cross-sectional study used total sampling on all medical records of international travelers visiting an international hospital in Bali. A total of 999 medical records were analyzed in this study. The mean age of the patients was 35.55 years. Most patients were female (53.9%) and used travel insurance (55.3%). Most health problems are complaints in the gastrointestinal system (22.3%). The primary health problem is the gastrointestinal system. Most patients use insurance to finance their health. Keywords: Health Problems, Travelers, Infectious and Non-Infectious